OVERVIEW OF THE SELF-CONCEPT OF TERRORISM INMATES IN AN EFFORT TO FULFILL THE RIGHT OF GUIDANCE IN CLASS IIA METRO PENITENTIARY - Wibowo, Anggara Dwi Panca Tri; Biafri, Vivi Sylviani (Journal of Management Small and Medium Enterprises (SMEs), 2025)
One of the greatest threats to Indonesia's security and sovereignty is the large-scale wave of terrorist groups. This study aims to obtain information on the self-concept of terrorist inmates in fulfilling their rehabilitation rights at the Class IIA Metro Penitentiary. To ensure that the collected data is rich in information and reliable for analysis, the primary focus of data collection includes both primary and secondary data. The data collection techniques used include semi-structured interviews, observation, and documentation. The data analysis technique involves data reduction, presentation in tables and graphs, and drawing conclusions. Ultimately, this study illustrates how the self-concept of terrorist inmates at the Class IIA Metro Penitentiary is shaped through interactions with their environment, involving internal dimensions such as identity, behavior, and self-assessment, as well as external dimensions, including ethical morals, physical aspects, and social aspects. Both participants demonstrated a good understanding of themselves, increased self-confidence, and positive changes in their self-perception and interactions with their environment. Keywords: Self-concept; Terrorism Inmates; Rehabilitation